Microfluidic blood vasculature replicas using backside lithography - Fenech, Marianne; Girod, Vincent; Claveria, Viviana; Meance, Sebastien; Abkarian, Manouk; Charlot, Benoit (Université d'Ottawa | University of Ottawa, 2019)
Blood vessels in living tissues are an organized and hierarchical network of arteries, arterioles, capillaries, veinules and veins. Their sizes, lengths, shapes and connectivity are set up for an optimum perfusion of the tissues in which they deploy. In order to study the hemodynamics and hemophysics of blood flows and also to investigate artificial vasculature for organs on a chip, it is essential to reproduce most of these geometric features. Common microfluidic techniques produce channels with a uniform height and a rectangular cross section that do not capture the size hierarchy observed in vivo. This paper presents a new single-mask photolithography process using an optical diffuser to produce a backside exposure leading to microchannels with both a rounded cross section and a direct proportionality between local height and local width, allowing a one-step design of intrinsically hierarchical networks.